THE IMPORTANCE OF CORRECTIONAL PEDAGOGY IN INCLUSIVE EDUCATION - Kurbanbaeva, Dilaram Mukhamovna (SCIENCE and SOCIETY, 2026)
This research is explored the role of correctional pedagogy in inclusive education. Inclusive education ensures every child’s right to learn, considering their individual needs. Correctional pedagogy supports academic achievement, social integration, and personal development.